x-6=-8x-6

Simple and best practice solution for x-6=-8x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-6=-8x-6 equation:


Simplifying
x + -6 = -8x + -6

Reorder the terms:
-6 + x = -8x + -6

Reorder the terms:
-6 + x = -6 + -8x

Add '6' to each side of the equation.
-6 + 6 + x = -6 + 6 + -8x

Combine like terms: -6 + 6 = 0
0 + x = -6 + 6 + -8x
x = -6 + 6 + -8x

Combine like terms: -6 + 6 = 0
x = 0 + -8x
x = -8x

Solving
x = -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
x + 8x = -8x + 8x

Combine like terms: x + 8x = 9x
9x = -8x + 8x

Combine like terms: -8x + 8x = 0
9x = 0

Divide each side by '9'.
x = 0

Simplifying
x = 0

See similar equations:

| 21+24x=17x+28 | | p+1+6p=4p-14 | | 23x+14y=283 | | 20-3m-1=-4 | | 3x+4(2x+2)=3 | | 4+5x=6+3x | | 4y+8=-26 | | 33+7x+10=13+2x | | 3.5(x+4)+4.5=2(-6.5) | | .66(1+n)=-.50n | | |-3a|=15 | | x^2+10+24= | | y=2/3(-1)-7 | | 9.06=51 | | -62u=60 | | 2y+6=-8 | | (x+4)(x-2)=7 | | y=2/3(1)-7 | | y=2/3(0)-7 | | 6b-38=-6b+14 | | 3(2x+1)=4x-13 | | 54=(4r-5) | | 8(f+8)=1 | | 2a-5(a-4)=-4 | | X+3x-12=180 | | 7=2t-5 | | X(3x-12)=180 | | 4x+(5+2x)=2 | | 5x+18-4=-36 | | x^2+6-30=0 | | 2r-45-19r=-53+r | | w-6=-48 |

Equations solver categories